1993
DOI: 10.1073/pnas.90.21.10375
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of interacting domains between the nucleocapsid protein and the phosphoprotein of vesicular stomatitis virus by using a two-hybrid system.

Abstract: Specific interaction between the nucleocapsid protein (N) and the phosphoprotein (P) of vesicular stomatitis virus (VSV), an important step in the life-cycle ofthe virus, was studied by using a two-hybrid system. Plasmids encoding P fused with the yeast GAL4 DNA-binding domain (pGALP) and N fused with the herpes simplex virus VP16 transactivating region (pVPN) were transfected into CHO cells along with a reporter plasmid encoding chloramphenicol acetyltransferase (CAT). The ability of N and P to associate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
68
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 28 publications
12
68
0
Order By: Relevance
“…This finding confirms those of several studies demonstrating that phosphorylation of the P's of rabies virus and Sendai virus is not required for their oligomerization (31-33), indicating that P of VSV behaves like the P's of rabies virus and Sendai virus. Furthermore, our in vivo coimmunoprecipitation assay also confirmed that N-terminal phosphorylation of P is dispensable for the interaction of P with N and L, although Gao and Lenard (14,15) proposed that N-terminal phosphorylation may be involved in interaction of P with L. Moreover, our results also support a previous study revealing that phosphorylation of VSV P is not required for N-P complex formation (34). Thus, the transcriptional inactivity of P3A in vivo may not be caused by its selfassociation, as it interacted with L and N.…”
Section: Discussionsupporting
confidence: 89%
“…This finding confirms those of several studies demonstrating that phosphorylation of the P's of rabies virus and Sendai virus is not required for their oligomerization (31-33), indicating that P of VSV behaves like the P's of rabies virus and Sendai virus. Furthermore, our in vivo coimmunoprecipitation assay also confirmed that N-terminal phosphorylation of P is dispensable for the interaction of P with N and L, although Gao and Lenard (14,15) proposed that N-terminal phosphorylation may be involved in interaction of P with L. Moreover, our results also support a previous study revealing that phosphorylation of VSV P is not required for N-P complex formation (34). Thus, the transcriptional inactivity of P3A in vivo may not be caused by its selfassociation, as it interacted with L and N.…”
Section: Discussionsupporting
confidence: 89%
“…Mammalian Two-hybrid Interaction Assay-The WT PACT and P222L ORFs were subcloned into pSG424 (Addgene) such that it produced an in-frame fusion to GAL4 DBD and in VP16 AD vector pVP16AASV19N (8,34) such that it produced an in-frame fusion to VP16 AD. Fusion proteins were tested for interaction in various combinations.…”
Section: Methodsmentioning
confidence: 99%
“…Similar systems based upon Gal4 and VP16 fusion proteins have been described recently whereby interactive domains of other viral proteins have been identified and mapped (Takacs et al, 1993). Our data support and extend those of Huber et al (1991), who utilized a biochemical approach to show that the Cterminal half of the P protein was important for binding to N. Although the involvement of the C-terminal region of VP16/P in binding to Gal4/N may have been anticipated, the importance of the NH2-terminal region of P in binding to N was unforeseen, since experiments to ascertain the importance of the NHz terminus of P in binding to N or to other measles virus proteins had yet to be performed.…”
mentioning
confidence: 89%
“…A more thorough understanding of the structural and functional domains of these key regulatory proteins of measles virus, and their homologues encoded by other negativestranded RNA viruses, will undoubtedly enhance our knowledge of paramyxovirus replication and pathogenesis. Toward this end, interactions among the N, P and L proteins of Sendai virus (Buchholz et al, 1994;Curran et al, 1994;Homann et al, 1991 ;Ryan & Portner, 1990;Ryan et al, 1991;Smallwood et al, 1994), vesicular stomatitis virus (Howard & Wertz, 1989;Takacs et al, 1993), rabies virus (Fu et al, 1994) and measles virus (Horikami et al, 1994;Huber et al, 1991) have been the focus of recent investigations. The COOH-* Author for correspondence.…”
mentioning
confidence: 99%